Association between Obesity and Carotid Intima-Media Thickness in Korean Office Workers: The Mediating Effect of Physical Activity. (1st August 2018) - Jin, Youngyun; Kim, Donghyun; Cho, Jinkyung; Lee, Inhwan; Choi, Kyuhwan; Kang, Hyunsik
Abstract : Background. Obesity and physical inactivity are associated with higher prevalence of cardiovascular disease (CVD). Objective. This study investigated the association between obesity and carotid intima-media thickness (CIMT) stratified by physical activity (PA) in Korean office workers. Methods. Data obtained from 914 office workers aged 21-60 years (347 women) were used. Resting blood pressures, body mass index (BMI), and waist-to-height ratio (WHtR) were measured. PA was assessed using the international physical activity questionnaire. CIMT was assessed with a carotid artery ultrasonography. Logistic regression analysis was used to estimate the odds ratio (OR) and 95% confidence interval (CI) of obesity stratified by weekly PA for an abnormally increased CIMT. Results. Logistic regression analyses showed that those who were overall obese (OR=2.50, 95% CI=1.60-3.91, P<0.001) or central obese (OR=2.08, 95% CI=1.29-3.40, P=0.003) had significantly higher estimated risks of having an abnormally increased CIMT even after adjustments for age, sex, smoking, alcohol consumption, resting blood pressures, and history of hypertension, diabetes, and hyperlipidemia, as compared with those who were not overall or central obese (OR=1). A multivariate linear regression suggested that age (P<0.001), sex (P=0.002), hypertension (P=0.014), smoking (P=0.054), BMI (P<0.001), and physical activity (P=0.011) were important determinants of abnormally elevated CIMT in this study population. Conclusion. The current findings suggest that the risk of obesity for an abnormally increased CIMT is significantly modulated by demographics as well as lifestyle-related risk factors including smoking and physical inactivity in Korean office workers.